The Effect of Covid-19 Pandemic on the Soundness of Islamic Banks in Indonesia - SISWANTORO SISWANTORO (Kunuz: Journal of Islamic Banking and Finance, 2022)
The purpose of this study is to answer the debate regarding the impact of the Covid-19 pandemic on the soundness of Islamic banks in Indonesia. In this study, the soundness of Islamic banking is measured using the RGEC method. The object of the research is focused on all Islamic banking companies operating in Indonesia with a total population of 14 companies. The data is the annual reports of the company in the period before and after the pandemic, namely the 2019 and 2020 periods. After the sample selection process was carried out, only 12 companies remained that met the criteria for further analysis. The data analysis technique used descriptive statistical analysis and different tests with paired sample t-test and Wilcoxon signed-rank test which had previously passed the normality test. The results showed that only the capital adequacy ratio indicator experienced significant differences before and after the Covid-19 pandemic in Indonesia, while the other three indicators showed no significant differences. This indicates that Islamic banking is still quite capable of overcoming the impact of the pandemic so that it does not have a serious effect on the soundness of Islamic banking.